2012
DOI: 10.1097/yco.0b013e3283523dcc
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of psychiatric and substance use disorders in the United States

Abstract: Purpose of review The comorbidity between psychiatric and substance use disorders remains an important phenomenon to understand, and an active area of investigation. The purpose of this review is to highlight key 2011 issues and novel findings on psychiatric and substance disorders comorbidity from the National Epidemiologic Survey on Alcohol and Related Conditions (NESARC), a large national survey of the US general population. Recent findings Topics of active investigation included the internalizing/externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(72 citation statements)
references
References 43 publications
2
63
0
3
Order By: Relevance
“…Those with comorbidity are also likely to be an important subgroup for prognosis or treatment response. Comorbidity is, unfortunately, the “norm” in psychiatric diagnosis [43, 44]. It clouds clinical taxonomic systems and complicates research.…”
Section: The Prevalence Of Aud In Pd and Pd In Audmentioning
confidence: 99%
“…Those with comorbidity are also likely to be an important subgroup for prognosis or treatment response. Comorbidity is, unfortunately, the “norm” in psychiatric diagnosis [43, 44]. It clouds clinical taxonomic systems and complicates research.…”
Section: The Prevalence Of Aud In Pd and Pd In Audmentioning
confidence: 99%
“…La coexistencia de trastornos por consumo de sustancias (TCS) con otros trastornos psiquiátricos (OTP), también conocida como Patología Dual (PD) (Szerman et al, 2013), ha sido ampliamente documentada desde los años 80, con los estudios de epidemiología psiquiátrica de tercera generación (Borges, Medina-Mora, & López-Moreno, 2004;Hasin & Kilcoyne, 2012;Hasin, Nunes, & Meylan, 2004;Kessler et al, 2004), que marcan un nuevo paradigma en la categorización de los trastornos mentales y sus comorbilidades. Aunque esto ha permitido avances en la comprensión de este fenó-meno, los grandes estudios epidemiológicos en psiquiatría se basan en encuestas realizadas en hogares y población universitaria (Grant & Dawson, 2006;Kessler et al, 2004;Demyttenaere et al, 2004), lo que limita el conocimiento sobre la salud mental en poblaciones marginadas (por ejemplo indigentes, reclusos, migrantes y refugiados) (Baxter, Patton, Scott, Degenhardt, & Whiteford, 2013).…”
Section: Introductionunclassified
“…Both epidemiological [1,2] and clinical [3,4] studies have reported that individuals diagnosed with severe mental illness (SMI) are more prone to substance use than are people without SMI. Individuals diagnosed with SMI are also at greater risk of hospitalization, homelessness and suicide [5], and experience more adversity in different arenas throughout life [6,7].…”
Section: Introductionmentioning
confidence: 99%